Dual-Band Metamaterial Microwave Absorber using Ring and Circular Patch with Slits - M. S. Sim; K. Y. You; R. Dewan; F. Esa; M. R. Salim; S. Y. N. Kew; F. Hamid (Advanced Electromagnetics, 2023)
This paper proposes a dual-band metamaterial microwave absorber operating at 2.5 GHz and 5.8 GHz. The absorber consists of a ring and a circular patch with slits resonator structures printed on a FR4 dielectric substrate backed by a ground layer. The main advantage of the absorber lies in its design flexibility in which each absorption band is independent and can be individually tuned by changing the dimensions of each resonator structure. The absorber unit cell is simulated and parametrically optimized using Computer Simulation Technology (CST) software. The absorption mechanism is analyzed through surface current analysis.  The absorber prototype, with dimensions of 200 × 200 × 1.6 mm3 and consisting of an array of 7 × 7 unit cells, is fabricated and experimentally investigated using antennas in free-space measurement. The absorber exhibits over 97% absorption at both resonance frequencies. Furthermore, the absorber is demonstrated to be applicable in sensing applications for dielectric constant determination. With its design simplicity, wide-angle receptive, and polarization insensitive behavior, it is envisaged that the proposed absorber will find practical use in absorbing and sensing applications.